Leadership in the U.S. Senate herding cats in the modern era - Campbell, Colton C. 1965- (Routledge, 2018)
Unlike leadership in the House of Representatives, the nature of Senate leadership continues to remain a mystery to so many. Due to the absence of an "operator's manual," leaders have had to use their individual skills, intelligence, and personalities to lead the Senate, which means they each have had their own unique leadership style. How have Senate majority leaders advanced their agendas in this traditionally egalitarian institution, a chamber like no other legislative body, where they must balance the rights of 99 independent senators with the collective needs of their party? Featuring a foreword by Senate Majority Leader Mitch McConnell, Leadership in the U.S. Senate offers students a comprehensive and contemporary examination of three different eras in the evolution of the Senate. Collectively, contributions written by those who have served the senators offer insight into how different Senate leaders have operated, chronicle changes in Senate life over the past four decades, and describe how they have changed the institution. The chapters cover: How leadership styles are shaped by both individualism and party goals. Eight biographical perspectives from Senator Howard Baker (R-TN) to Senator Harry Reid (D-NV). The political context of the Senate during which the respective majority leader served Individual leadership style and performance in office Contributions individuals made to the institution while serving as majority leaders. This book paves the way for political scientists and others to examine the topic of Senate leadership